Evaluation of early vigor under direct planting cultivation in sweet potato. (2nd January 2021) - Sakaigaichi, Takeo; Kai, Yumi; Kobayashi, Akira; Suematsu, Keisuke
ABSTRACT: Direct planting – in which small storage roots are planted instead of transplanting stem cuttings – has been studied as a labor-saving system in sweet potato. Early vigor is important for cultivars used in direct planting because it affects their ability to compete with weeds. In this study, the genotypic difference in early vigor was evaluated. Twelve genotypes were tested in 2018 and 2019. Days to emergence, shoot dry matter yield, plant height, and NDVI were investigated as indicators of early vigor. Significant differences in days to emergence and shoot dry matter yields were observed among genotypes in both years. 'Kyushu No.198ʹ was outstanding in terms of early vigor. A strong relationship between plant height and shoot dry matter yield was observed; this relationship was also observed with NDVI. Growth traits that can be monitored in a non-destructive way, such as plant height, are reliable predictors of shoot dry matter yield during early growth.